Engaging Patients in their Health Care: Lessons From a Qualitative Study on the Processes Health Coaches Use to Support an Active Learning Paradigm - Karen L Caldwell PhD; Delia Vicidomini BS; Reese Wells BS; Ruth Q Wolever PhD (SAGE Publishing, 2020)
Background While recent health-care trends rely on activated patients, few studies report direct observations of how to engage and activate patients to be full participants in their own health care. The interpersonal processes and communication strategies used in integrative health coaching (IHC) may offer important insight into how clinicians can help patients step into a more active learning model rather than more typical passive roles. Objective This study uses verbatim transcripts of medical patients' first few IHC sessions to identify the actual processes used to help patients embrace this more active learning role. Methods A thematic analysis was conducted of 72 verbatim transcripts from IHC sessions of 26 patients with severe dysfunction from tinnitus. The patients participated in 6 months of IHC as part of a larger integrative intervention in a randomized, controlled pilot designed to assess feasibility for a larger randomized, controlled trial on the clinical effectiveness of an integrative intervention. Results Four themes emerged: (1) Describing the Health Coaching Process to patients; (2) Using Key Procedures for Action Planning-optimal health future self-visualization, Wheel of Health, and exploration of the gap between current and desired states to help patients set goals for themselves; (3) Supporting Action and Building Momentum-the creation and support of action steps with frequent reinforcement of self-efficacy; and (4) Active Listening and Inviting the Patient to Articulate Learning-coaches' active listening process included reflection, clarifying questions, turning patient questions back to the patients, highlighting values, identifying potential barriers and resources, and inviting patients to articulate what they were learning. Conclusion The processes identified in IHC incorporate key principles of adult learning theory and engage patients' innate resources of goal orientation, self-direction, and intrinsic motivation. These interpersonal processes help patients embrace a more active learning role, with implications for patient engagement in other clinical contexts.